TARIXIY VOQEALAR VA IXTIROLARNING ZAMONAVIY NUTQ TERAPIYASIGA TA’SIRI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article explores the essence, goals, and practical significance of speech therapy while analyzing the historical events and innovations that shaped its modern development. It highlights early scientific perspectives on speech disorders, the contributions of 19th-century phonetics, clinical insights gained during the world wars, and the transformative role of contemporary technologies. Modern speech therapy is presented as a comprehensive system grounded in accurate diagnosis, rehabilitation, and innovative therapeutic approaches. The article emphasizes the importance of speech therapy in improving communication abilities, social integration, and overall quality of life.